'But if Taiwan legalizes same-sex marriage … ': discourses of homophobia and nationalism in a Chinese antigay community online. Issue 4 (4th July 2021) - Liu, Xuekun
ABSTRACT: This article examines the interplay between homophobia and nationalism by analyzing online comments on the ruling of legalizing same-sex marriage in Taiwan. Drawing on methods from critical discourse analysis, I focus on the framing of this ruling by members from a Chinese antigay community online. I show that they frame this ruling as (1) in opposition to public opinion, (2) promoting 'Westernization' and 'Independence', (3) seeking immorality and self-destruction. I find that within these frames, they evoke nationalist discourses that represent supporters of this ruling as the 'Other' who attempt to split with China, thereby associating LGBT equality movements in China with this political threat. I argue that these nationalist discourses are used in a way that reinforces and legitimizes discourses of homophobia.